Wildfires Dynamics in Siberian Larch Forests - Evgenii Ponomarev; Viacheslav Kharuk; Kenneth Ranson (Forests, 2016)
Wildfire number and burned area temporal dynamics within all of Siberia and along a south-north transect in central Siberia (45°–73° N) were studied based on NOAA/AVHRR (National Oceanic and Atmospheric Administration/ Advanced Very High Resolution Radiometer) and Terra/MODIS (Moderate Resolution Imaging Spectroradiometer) data and field measurements for the period 1996–2015. In addition, fire return interval (FRI) along the south-north transect was analyzed. Both the number of forest fires and the size of the burned area increased during recent decades (p < 0.05). Significant correlations were found between forest fires, burned areas and air temperature (r = 0.5) and drought index (The Standardized Precipitation Evapotranspiration Index, SPEI) (r = −0.43). Within larch stands along the transect, wildfire frequency was strongly correlated with incoming solar radiation (r = 0.91). Fire danger period length decreased linearly from south to north along the transect. Fire return interval increased from 80 years at 62° N to 200 years at the Arctic Circle (66°33’ N), and to about 300 years near the northern limit of closed forest stands (about 71°+ N). That increase was negatively correlated with incoming solar radiation (r = −0.95).